Liquified capsules containing nanogrooved microdiscs and co-encapsulated endothelial and mesenchymal stem cells for bone tissue engineering - Carreira, Mariana da Silva (2020)
The emerging of the Tissue Engineering field led to the substitution of natural bone grafts by engineered ones, termed as scaffolds. Scaffolds are temporary structures that can be combined with cells, and include biochemical or biophysical cues to promote the regeneration of tissues. Surface topography has been shown to influence cell behavior and direct the differentiation of mesenchymal stem cells (MSCs) into distinct lineages. Whereas this has been verified in a bi-dimensional (2D) context, the role of topography in tri-dimensional (3D), which better mimics the natural cell environment, needs to be explored. Therefore, the main goal of this work is to incorporate topographical featured microparticles in a 3D system, and to assess their ability to guide MSCs osteoblastic differentiation in the absence of osteogenic differentiation factors. A co-culture of Wharton’s jelly-derived mesenchymal stem cells (WJ-MSCs) and human umbilical vein endothelial cells (HUVECs) is encapsulated in a 3D system. Such system consists in a permselective liquified environment containing freely dispersed spherical microparticles (spheres) or nanogrooved microdiscs (microdiscs). Microdiscs presenting 358±23 nm grooves and 944±49 nm ridges are produced via nanoimprinting of spherical polycaprolactone microparticles between water-soluble polyvinyl alcohol counter-moulds of optical media (CDs). Spheres and microdiscs are cultured in vitro in basal or osteogenic media for 21 days. It is hypothesized that, without additional osteogenic differentiation factors, the topographical features present in the microdiscs would induce the osteoblastic differentiation of adhered WJ-MSCs through contact guidance. Results show an enhanced osteoblastic differentiation in microdiscs compared to spheres, even in basal medium, evidenced by ALP activity and extracellular matrix deposition. The developed 3D bioencapsulation system comprising nontopographical features might be suitable as smart and autonomous bone tissue engineered approaches requiring minimum in vitro manipulation.